2016
DOI: 10.1111/bju.13676
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Health Index improves multivariable risk prediction of aggressive prostate cancer

Abstract: Objective To examine the use of the Prostate Health Index (phi)* as a continuous variable in multivariable risk assessment for aggressive prostate cancer in a large multicenter US study. Materials and Methods The study population included 728 men with PSA levels of 2-10 ng/mL and negative digital rectal examination enrolled in a prospective, multi-site early detection trial. The primary endpoint was aggressive prostate cancer, defined as biopsy Gleason score ≥7. First, we evaluated whether the addition of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 24 publications
0
61
0
1
Order By: Relevance
“…79,80 Additionally, in a large, multicentre, prospective study, PHI significantly improved the performance of the PCPT and ERSPC risk calculators (see below) in men with a PSA between 2 and 10 ng/ml for predicting the risk of Gleason ≥7 prostate cancer. 81 A multicentre cohort study evaluating the clinical utility of PHI found that it reduced unnecessary biopsies by 36% and only missed 2.5% of highgrade cancers. 80 When comparing PHI and the 4K score, the two tests appear to demonstrate similar discriminatory ability in predicting high-risk prostate cancer in men with a PSA between 3 and 15 ng/ml (AUC 4Kscore 0.718 vs. PHI 0.711).…”
Section: Prostate Health Index (Phi ® )mentioning
confidence: 99%
“…79,80 Additionally, in a large, multicentre, prospective study, PHI significantly improved the performance of the PCPT and ERSPC risk calculators (see below) in men with a PSA between 2 and 10 ng/ml for predicting the risk of Gleason ≥7 prostate cancer. 81 A multicentre cohort study evaluating the clinical utility of PHI found that it reduced unnecessary biopsies by 36% and only missed 2.5% of highgrade cancers. 80 When comparing PHI and the 4K score, the two tests appear to demonstrate similar discriminatory ability in predicting high-risk prostate cancer in men with a PSA between 3 and 15 ng/ml (AUC 4Kscore 0.718 vs. PHI 0.711).…”
Section: Prostate Health Index (Phi ® )mentioning
confidence: 99%
“…[19, 20, 33, 34] As an example, adding PHI to the PCPT-RC or ERSPC-RC improves the predictive accuracy of aggressive disease. [35]…”
Section: Determining the Need For Prostate Biopsymentioning
confidence: 99%
“…More recently, Loeb et al developed a new nomogram using phi with other variables to predict clinically significant PCa. (27)…”
Section: Blood Biomarkersmentioning
confidence: 99%